Dermatite de Duhring-Brocq - Volpato, Solange Emanuelle; Azevedo Raiol, Theisla Kely; Mendes da Silva Dantas, Mecleine; Andrade de Almeida Lopes, Maria Luciana; Sousa Medeiros Torres Ferreira, Isabelle; Volpato, Bruna Heloisa (Clinical and Biomedical Research, 2014)
The authors describe two cases of Duhring-Brocq dermatitis, one in a child of 6 years and the other for young adults. The child due to a recurrent condition and injury to their daily activity beyond the gluten-free diet was prescribed Dapsone.